2022
DOI: 10.3390/molecules27196476
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Analyses Provide Insights into the Flavonoid Accumulation in Peels of Citrus reticulata ‘Chachi’

Abstract: The quality of Chinese medicinal materials depends on the content of bioactive components, which are affected by the environmental factors of different planting regions. In this research, integrated analysis of the transcriptome and metabolome of C. reticulata ‘Chachi’ was performed in two regions, and three orchards were included in the analysis. In total, only 192 compounds were found in fresh peels, and among 18 differentially accumulated flavonoid metabolites, 15 flavonoids were enriched in peels from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The expression levels of regulating genes such as AP2/ERF-ERF , LIM , and HB-HD-ZIP were greater in the Xinhui region than in other regions. Similarly, more flavonoids accumulated in the peel of CRC from Xinhui region than those from other regions 58 . These findings suggested that increased expression of AP2/ERF-ERF , LIM , and HB-HD-ZIP might contribute to increased abundance of flavonoids.…”
Section: Discussionmentioning
confidence: 87%
“…The expression levels of regulating genes such as AP2/ERF-ERF , LIM , and HB-HD-ZIP were greater in the Xinhui region than in other regions. Similarly, more flavonoids accumulated in the peel of CRC from Xinhui region than those from other regions 58 . These findings suggested that increased expression of AP2/ERF-ERF , LIM , and HB-HD-ZIP might contribute to increased abundance of flavonoids.…”
Section: Discussionmentioning
confidence: 87%
“…It catalyzed the formation of chalcone, a substance from which different flavonoids were derived [83]. The overexpression of EaCHS1 in peels of C. reticulata 'Chachi' increased the production of downstream flavonoids and the expression of related genes in the phenylpropanoid pathway [84]. There was a substantial positive association between SeCHS1 and five flavonoid compounds in Sechium edulel [85].…”
Section: Discussionmentioning
confidence: 99%
“…Mohammady et al [25] reported significant upregulations of IGF-2, SOD, CAT, and GH gene expressions in the Nile tilapia fish fed diets containing varying amounts of LOG (10, 20, and 30 ml LOG/ Kg) compared to the control group, with the highest gene expressions observed in fish fed a diet containing 20 ml LOG Kg. Aanyu et al [46] similarly noted significant enhancements in the expression of the IGF-1 gene in Nile tilapia fish fed 0.00 0.50 [88] and Nile tilapia [90] farmed in aquaculture and flavonoids found in Citrus reticulata "chachi" peels caused significant alterations in numerous gene expressions related to salt stress response [91,92].…”
Section: Gh Gene Expressionmentioning
confidence: 99%